Effect of Perceived Healthcare Service Quality on Patient Loyalty Mediated by Patient Satisfassction at XY Hospital (Servqual Dimensional Approach) - Lidya Suryany Holiwono; Pauline H. Pattyranie Tan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine 1) the effect of hospital safety on patient satisfaction, 2) the effect of infrastructure on patient satisfaction, 3) the effect of staff competence on patient satisfaction, and 4) the influence of hospital safety, infrastructure and staff competence on patient loyalty mediated by patient satisfaction. At XY Hospital. The results of the study show several findings 1) the effect of hospital safety on patient satisfaction shows that the relationship between the two is positive 2) the influence of infrastructure on patient satisfaction shows that the quality of infrastructure increases, patient satisfaction also increases, 3) the influence of staff competence on patient satisfaction shows a direct influence by staff competence on patient satisfaction, 4) the effect of patient satisfaction on patient loyalty shows that patient satisfaction has a significant and positive effect on patient loyalty, the effect of hospital safety on patient loyalty mediated by patient satisfaction shows that health services affect patient loyalty through patient satisfaction. The effect of infrastructure on patient loyalty mediated by patient satisfaction shows that there is an indirect effect of hospital infrastructure on patient loyalty mediated by patient satisfaction. The effect of staff competence on patient loyalty by mediating patient satisfaction shows that there is a significant indirect effect of staff competence on patient loyalty mediated by patient satisfaction.